Motivación y productividad de los trabajadores de la Municipalidad Distrital de Belén área administrativa 2025 - Pezo Runciman, Samantha (2025)
The primary objective was to determine the relationship between motivation and job productivity among the administrative workers of the District Municipality of Belén during the year 2025. The study was essentially descriptive and correlational, focusing on quantitative aspects while avoiding experimental design, using a cross-sectional approach that allowed for the analysis of variables in their natural state without manipulation. To evaluate the association between motivation and job productivity, the Spearman Rho correlation coefficient was applied. The results showed a very strong and statistically significant positive correlation (r = 0.948, p = 0.000), confirming the proposed hypothesis. This indicates that a higher level of job motivation is directly associated with an increase in the productivity of administrative workers. It is concluded that motivation is a determining factor for optimizing work performance; therefore, it is recommended that the District Municipality of Belén implement motivational strategies aimed at fostering a favorable work environment that contributes to institutional development. This study provides relevant quantitative evidence for human resource management, highlighting the importance of workplace well-being as a foundation for improving organizational outcomes.